Diabetes care in a complex humanitarian emergency setting: a qualitative evaluation - Adrianna Murphy; Michel Biringanine; Bayard Roberts; Beverley Stringer; Pablo Perel; Kiran Jobanputra (BMC, 2017)
Abstract Background Evidence is urgently needed from complex emergency settings to support efforts to respond to the increasing burden of diabetes mellitus (DM). We conducted a qualitative study of a new model of DM health care (Integrated Diabetic Clinic within an Outpatient Department [IDC-OPD]) implemented by Médecins Sans Frontières (MSF) in Mweso Hospital in eastern Democratic Republic of Congo (DRC). We aimed to explore patient and provider perspectives on the model in order to identify factors that may support or impede it. Methods We used focus group discussions (FGDs; two discussions, each with eight participants) and individual semi-structured qualitative interviews (seven patients and 10 staff) to explore experience of and perspectives on the IDC-OPD. Participants were recruited purposively to represent a range of DM disease severity and staff functions respectively, and to ensure the age and gender distribution was representative of the population of DM patients registered in the clinic. Data were coded in NVivo10© and analysed using an inductive thematic approach. Results There appears to be little awareness surrounding DM in patient communities, resulting in delays presenting to hospital. Patients describe their first reactions to symptoms as fear and confusion, often assuming symptoms are of another disease (e.g. HIV/AIDS). They often express disbelief that they could have DM (e.g. stating DM is a 'rich man's disease') and lack acceptance that there is no cure. Patients experienced difficulty travelling to appointments, exacerbated by flare-ups in the conflict. Providing psycho-social and sensitisation activities in a group setting appears to offer an opportunity for patients to support each other in their effort to adhere to drug treatment and follow-up appointments. All patients reported great difficulty in adhering to the recommended diet, which was viewed as unaffordable and unavailable, and fear that this would be the biggest obstacle to maintaining their drug treatment (as treatment must be taken with food). Conclusion Our findings emphasize the importance of community awareness of DM and the value of treatment support, including psychosocial and educational support to DM patients and their families, and culturally sensitive, low-cost dietary advice, to ensuring the adoption and maintenance of DM treatment.